Survey of pathological manifestations in Santa Isabel bridge, through damage map (Research, Society and Development, 2022)
Bridges bring logistics benefits to society that influence the economy and its development. For this reason, bridges are so important for the growth of the region where they are located. Based on this, studies are needed that help to better understand the functioning of these structures, helping in the search for the best way to care for and preserve the useful life of their materials, so that they can provide the population with safety and practicality. Seeking to analyze the condition of the facade and structure of the Santa Isabel bridge, a study was developed regarding its conditions, adopting the method of elaboration of a damage map, which consists of mapping the points where pathological manifestations are found. For the study, the elaboration of data identification sheets was adopted, serving as an aid in the preparation of damage maps. The files are descriptive memorials of the situation of the bridge, made with the help of visual inspections, enriched with photographs of the data collected. In this work, it was possible to analyze the situation of the bridge in the years 2021 and 2022, making it possible to make a comparison of the evolution of pathological manifestations in this period. When all the information was verified and the comparisons were made, it was possible to notice the precarious state of the bridge structure, making evident the need for repairs and the elaboration of a preventive maintenance plan so that the manifestations do not repeat themselves so often.